Railway Line ’Zagreb-Rijeka’ - Marković, Ivo; Vučić, Dalibor; Muić, Mirela (Promet - Traffic&Transportation, 2004)
The current condition of the Zagreb - Rijeka railway line,and the throughput capacity of the line on the Botovo - Rijekasection reflect the overall situation of the railway traffic on thesection of the Corridor Jib. The existing condition needs to bereconstmcted by investing in the infra- and supra-structure.Along with the modernisation the increasingly present environmentalawareness should bring to the gradual shift of cargofrom road to railways. Such principle would contribute to theincrease in passenger traffic and eventually of the maritimetraffic as well.